Soft skills of human resources and their role in strategic performance Field research in a sample of the directorates of the Ministry of Education - khamees, Luma hadi; Al-Zeidi, Nadhum Jawad Abid (Journal of Economics and Administrative Sciences, 2020)
The research aims to analyze the relationships of influence and influence between the soft skills of human resources and strategic performance, as the soft skills of human resources constitute the engine for all duties and operations carried out by the organization, and as a result of sharp changes in the environment, it was necessary for this organization to determine the most important financial and non-financial indicators that are required Approving it in achieving strategic performance to ensure its survival and continuity in work. The research problem was represented by a decrease in cognitive awareness of the importance of employing soft skills for human resources in achieving the indicators of strategic financial and non-financial performance, so the importance of research emerges in an attempt to provide therapies for them, and to achieve the goals of the research by clarifying the relationship between the main and secondary research variables, the descriptive analytical approach has been adopted In the application of the research, as the questionnaire was used as a tool to collect data, which was prepared using ready-made measures, and a sample of (101) section managers and division officials were distributed in (6) directorates of the Iraqi Ministry of Education. For processing and analyzing research data, the statistical program (SPSS-V23) & (Excel) was used. Statistical methods also produced a set of results that confirmed the correlation between the soft skills of human resources and strategic performance, and there is also a significant effect of the soft skills of human resources in strategic performance. Among the most important limitations of the research is the scarcity of Iraqi research and studies specifically related to the soft skills of human resources, the difficulty of translating some foreign terms, and the difficulty of persuading the respondents to fill out the questionnaire paragraphs. As for the scientific implications of the research, it was represented by presenting a set of conclusions, the most important of which is that soft skills for human resources are the most important resources for identifying and building indicators of strategic financial and non-financial performance in light of the dynamic environment, which requires them to pay attention to developing soft skills by looking at the experiences of developed countries and trying to benefit from them. And apply them in the Iraqi environment in the best possible way. With regard to originality/value of the research, it is his attempt to combine two variables (soft skills for human resources and strategic performance) into one research to provide a contribution to providing a new source of its kind for the Iraqi and Arab library.